Classificatory Smoothing of Income with Extraordinary Items: A Reply. - Barnea, Amir; Ronen, Joshua; Sadan, Simcha (The Accounting Review, 1977)
Abstract The article deals with comments related to two major issues. Firstly, whatever results are obtained, they are consistent with the hypothesis and secondly, the rarity of the phenomenon under investigation. This might suggest insufficient data on which conclusions can be significantly based or that the subject matter is of a minor importance that it does not warrant a study. The first issue suggests that correlation analysis is not appropriate for tests of smoothing behavior if managements' intentions to smooth are not established independently. The commentor suggests that in the case of extraordinary items, any established correlation, whether positive or negative, of such items with either ordinary or net income statistics would point to a possible smoothing behavior, but of different types. Regarding the second issue, authors point out that extraordinary items incorporate three different variables namely nonrecurring expense adjusted for average tax rate, nonrecurring expense net of taxes and nonoperating expense adjusted for the average tax rate derived from basic data items.